MALAT1 long non-coding RNA and breast cancer. Issue 6 (3rd June 2019) - Arun, Gayatri; Spector, David L.
ABSTRACT: Non-coding RNAs are becoming major players in disease pathogenesis such as cancer. Metastasis Associated Lung Adenocarcinoma Transcript 1 (MALAT1) is a nuclear enriched long non-coding RNA that is generally overexpressed in patient tumors and metastases. Overexpression of MALAT1 has been shown to be positively correlated with tumor progression and metastasis in a large number of tumor types including breast tumors. Surprisingly, a recent report by Kim et al shows a metastasis suppressive role for Malat1 . Here, we discuss these results in the context of a large body of published literature that support a pro-tumorigenic role for MALAT1 in order to gain potential insights into the basis of these observed differences.